Islam, Development, and the Muslim Filipinos - Gowing, Peter G. (Silliman Journal, 2024)
Over the years, as a student of Muslim Filipino affairs, the writer has inquired into the past and present economic, political, social, and religious situation of the Moros. He has to reflect to some extent on the role that Islam plays in their desire and effort to improve materially and spiritually their life situation- which is waht he understands by development. This essay, then, offers some of the information and insights he has aqcuired about Islam and development, particularly with regard to Muslims in the Philippines. The essay focuses on three aspects of this large subject: First, some comments on Islam and development in general; Second, some reflections on the struggle of Muslim FIlipinos to develop in accord with the Islamic ideals of developmentl Third, some thoughts about the future of development for the Muslims in this land.